Evaluation of Anti-inflammatory Activity of Methanolic Extractof Solanum nigrum(Solanaceae): Anti-inflammatory effect of Solanum nigrumLinn extract - Ganesan Arunachalam; Natesan Subramanian; Gururaja Perumal Pazhani; Manickam Karunanithi; Vellayutham Ravichandran (Iranian Journal of Pharmaceutical Sciences, 2009)
The methanolic extract of whole plants of Solanum nigrumL. was investigated for anti-inflammatory activity on the experimental animal models. The methanolic extract at a concentration of 100 mg.kg-1and 200 mg.kg-1, p.o.showed the significant dose dependent anti-inflammatory activity in carrageenin and egg white induced hind paw oedema in rats. Anti-inflammatory activity of the tested extract was comparable with that of the standard drug indomethacin (10 mg.kg-1) and cyproheptadine (8mg.kg-1). The results lend support to the traditional use of Solanum nigrumin the treatment of inflammatory diseases